Interpreting Canada’s 2019 Food Guide and Food Labelling for Health Professionals - Lapum, Jennifer L.; St-Amant, Oona; Hughes, Michelle (Open textbook library., 2019)
This textbook provides the novice learner with a foundational understanding of Canada’s 2019 Food Guide and Food Labelling. It highlights important considerations for future health professionals seeking to adopt the new food guide into their practice, including strategies towards healthy eating. This open textbook underscores a relational inquiry approach to inform discussions with clients about nutrition and healthy eating.